EFFECTIVENESS OF CONCH BLOWING PRACTICE IN IMPROVING THE PULMONARY FUNCTIONS IN REGULAR SMOKERS WITH MILD-TO-MODERATE CHRONIC OBSTRUCTIVE PULMONARY DISEASE - SAI SAILESH KUMAR GOOTHY; VAMSIKRISHNA DONEPUDI; BHAGYASHREE NELLIKALAYA; JAGADEESH POLICHERLA; ANITA LAKSHMI; RAMAPRABHA PRABHAKAR; VIJAYARAGHAVAN RAJAGOPALAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present study was undertaken to observe the efficacy of 24 weeks of conch-blowing practice as an alternative therapy in improving the pulmonary functions of regular smokers with mild to moderate chronic obstructive pulmonary disease (COPD). Methods: In this study, a total of 30 male regular smokers with mild to moderate COPD were recruited from the Department of Pulmonary Medicine, NRI Institute of Medical Sciences, Visakhapatnam, Andhra Pradesh, after obtaining voluntary, written informed consent. The participants were trained for a week on blowing a conch. The intervention duration was 6 weeks, with 2 sessions a day, morning and evening, for 5 days a week. Each session comprises blowing the conch 3 times with a duration of 10 s. Vital capacity, 40 mmHg test, breath holding time, inspiration, and expiration were recorded and compared. Results: Following the intervention, the experimental group significantly improved in all respiratory parameters, such as vital capacity and 40 mmHg test values, breath-holding time inspiration, and expiration. No adverse effects were observed in the participants during the study period. Two-way repeated measures analysis of variance did not show statistical significance among overall group comparisons in the vital capacity (p=0.697). The overall test comparison showed significance (p<0.001). Conclusion: This study may conclude that significant improvement in respiratory parameters in the experimental group following the intervention. The study results may provide preliminary support for the efficacy of conch blowing in improving pulmonary function in regular smokers with mild-to-moderate COPD. Further detailed studies were recommended.